1998
DOI: 10.1144/gsl.sp.1998.140.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Localized shock- and friction-induced melting in response to hypervelocity impact

Abstract: The distribution of shock veins, friction melts and cataclastic rocks in complex impact craters reflects the response of target lithologies to varying rates of strain. Within the Sudbury impact structure, thin (<2 mm), anastomosing veins, which can define shatter cone surfaces, permeate the target rocks in a c. 15 km wide zone around the Sudbury igneous complex (SIC). A similar relationship exists within the Vredefort impact structure, with the additional association of the high-pressure SiO2 polymorphs coesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…It is generally considered that the effects of the modification stage are governed by the size of the transient cavity and the properties of the target rock lithologies (Melosh 1989). However, mapping at Haughton suggests that structures such as radial faults and detachment faults generated during the excavation stage play an important role during the modification stage, including reducing the overall strength of the target sequence prior to crater collapse , as has been documented at other impact structures (Spray 1997(Spray , 1998Spray et al 2004).…”
Section: Conceptual Cratering Model For the Haughton Impact Eventmentioning
confidence: 95%
“…It is generally considered that the effects of the modification stage are governed by the size of the transient cavity and the properties of the target rock lithologies (Melosh 1989). However, mapping at Haughton suggests that structures such as radial faults and detachment faults generated during the excavation stage play an important role during the modification stage, including reducing the overall strength of the target sequence prior to crater collapse , as has been documented at other impact structures (Spray 1997(Spray , 1998Spray et al 2004).…”
Section: Conceptual Cratering Model For the Haughton Impact Eventmentioning
confidence: 95%
“…Shock-wave interactions between different shock impedance materials may cause localized melting, which is most pronounced at the interface of metal-troilite and silicates, and the interface of minerals and pore space (Kieffer 1971;Stöffler et al 1991;Schmitt 2000;Sharp and De Carli 2006). Friction by shear along the contacts of materials of vastly contrasting shock impedance and along fractures may also produce local melting (Gault et al 1968;Kieffer 1975;Grady et al 1975;Spray 1998;Kenkmann et al 2000). Adiabatic shear can produce temperatures that are thousands of degrees hotter in shear regions than in immediately adjacent material (Grady et al 1975).…”
Section: Melt-vein Formation and Quenchmentioning
confidence: 99%
“…There has been a tendency in the literature to consider endogenic and impact-related pseudotachylites as distinct, with the former supposedly being of frictional origin and the latter being shock generated (Spray, 1998). Some authors have shown that at least two generations of pseudotachylites form during an impact and have to be considered separately (Lambert, 1981;Martini, 1978Martini, , 1275Martini, 1991Wiest, 1987;Hilke, 1991;Spray, 1998). The first generation has been referred to as type-A pseudotachylite (Martini, 1978(Martini, , 1991, type A and Bl pseudotachylite (Lambert, 1981), or S-type (shock-related) pseudotachy Iite (Spray, 1998).…”
Section: Pseudotachylitesmentioning
confidence: 99%
“…The aforementioned pseudotachylites stand opposed to the socalled type-B (Martini, 1978), type-B2 (Lambert, 1981), or E-type (endogenic related) pseudotachylites (Spray, 1998). They postdate the former ones and are believed to form during the modification stage of the cratering process when gravity-driven faulting leads to the collaps of the transient cavity.…”
Section: Pseudotachylitesmentioning
confidence: 99%